2015
DOI: 10.1016/j.cell.2015.01.022
|View full text |Cite
|
Sign up to set email alerts
|

GABA Blocks Pathological but Not Acute TRPV1 Pain Signals

Abstract: Sensitization of the capsaicin receptor TRPV1 is central to the initiation of pathological forms of pain, and multiple signaling cascades are known to enhance TRPV1 activity under inflammatory conditions. How might detrimental escalation of TRPV1 activity be counteracted? Using a genetic-proteomic approach, we identify the GABAB1 receptor subunit as bona fide inhibitor of TRPV1 sensitization in the context of diverse inflammatory settings. We find that the endogenous GABAB agonist, GABA, is released from nocic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
133
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(139 citation statements)
references
References 65 publications
6
133
0
Order By: Relevance
“…GABAB receptors are abundantly expressed in DRG neurons [11], particularly in the cell bodies and peripheral terminals of nociceptive neurons expressing polymodal noxious sensory channel TRPV1 [10]. While at the moment there is no widely accepted theory for the potential source of GABA in the periphery, study by Hanack and colleagues suggested that nociceptive neurones themselves can produce GABA and release it at the level of peripheral terminals in response to noxious stimulation; these authors further suggested that such peripherally-released GABA acts in an autocrine way to counteract sensitization of TRPV1 channels and reduce hyperalgesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GABAB receptors are abundantly expressed in DRG neurons [11], particularly in the cell bodies and peripheral terminals of nociceptive neurons expressing polymodal noxious sensory channel TRPV1 [10]. While at the moment there is no widely accepted theory for the potential source of GABA in the periphery, study by Hanack and colleagues suggested that nociceptive neurones themselves can produce GABA and release it at the level of peripheral terminals in response to noxious stimulation; these authors further suggested that such peripherally-released GABA acts in an autocrine way to counteract sensitization of TRPV1 channels and reduce hyperalgesia.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, cell bodies of sensory neurons express various receptors for classical neurotransmitters such as acetylcholine, glutamate and GABA [5]. Particularly, both GABAA [6,7,8,9] and GABAB [10,11] receptors are abundantly expressed in somatosensory neurons, including nociceptors. A recent study demonstrated that peripheral nociceptive terminals are capable of releasing GABA, which acts in an autocrine fashion at the endogenous GABAB1 receptors to attenuate sensitization of heat-and inflammation-activated TRPV1 channels thus limiting hyperalgesia in rats [10].…”
Section: Introductionmentioning
confidence: 99%
“…91 Here, activated GABA B1 inhibits TRPV1 sensitization and inflammatory pain caused by inflammatory mediators by preventing TRPV1 phosphorylation. It will be interesting to know whether GABA B1 acts by interfering in the interaction between TRPV1 and AKAP79/150.…”
Section: Modulation Of Trpv1mentioning
confidence: 99%
“…This eliminates the need for extensive purification and greatly increases the confidence in the data. However, so far this was largely limited to the analysis of single bait proteins in vivo (23,24). To our knowledge, the approach has not yet been employed for systematic in vivo PPI mapping in C. elegans early embryos.…”
mentioning
confidence: 99%